Acceptable Threshold of Parking Charges for Urban Electric Bicycles - Deng, Yajuan; Wang, Ting; Ma, Rui (Promet - Traffic&Transportation, 2019)
Electric bicycles are one of the essential traffic modes in many cities in China. Due to the consideration on safety and efficiency of the urban transportation systems, it is recognized that the use of electric bicycles should be limited by shifting the demand towards public transit by imposing parking charges on electric bicycles. To plan for this, the travellers’ acceptance of parking charges must be taken into account. This paper proposes an acceptable threshold Logit model based on the non-compensation theory to calculate the threshold of the parking charge of electric bicycles. Electric bicycle trips are categorized into seven groups in terms of travel distances. The parking charges are of four discrete levels, from 0, 1, 2 to 3 yuan. Based on the survey data in the city of Handan, the traditional and acceptable threshold Nest-Logit models with the distance intervals and charges have been established and calibrated. Model calibration results show that the acceptable threshold Nest-Logit model is more accurate than the traditional Nest-Logit model, and the parking charge thresholds do exist. Specifically, within 3 km and outside 3 km the parking charge threshold is 1 yuan and 2 yuan, respectively. The parking charge thresholds can help in decision-making for parking pricing of electric bicycles.